2019
DOI: 10.1186/s13293-019-0246-6
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones, aging and cardiometabolic syndrome

Abstract: It is well documented that the metabolic syndrome predisposes patients to increased cardiovascular risk. Emerging data indicates that cardiovascular risk conferred by metabolic syndrome is highly dependent on sex and sex hormone status throughout the lifetime. Both male and female sex hormones, as well as sex chromosomes themselves, contribute to the development of obesity and intervene in the control of insulin homeostasis and blood pressure. Furthermore, men and women develop age-associated cardiometabolic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(76 citation statements)
references
References 117 publications
3
65
1
7
Order By: Relevance
“…4 There is also a strong relationship between MS and developing DM, which intensifies the greater MS component number. 21 Alone, SAH already confers a cardiometabolic risk, which can further impair insulin resistance in the metabolism of individuals with MS. 34 The results of this study showed that the hypertensive elderly individuals with MS and those who are obese had higher FRSs. MS significantly increased the chance of the elderly having a high CVR.…”
Section: Discussionmentioning
confidence: 63%
“…4 There is also a strong relationship between MS and developing DM, which intensifies the greater MS component number. 21 Alone, SAH already confers a cardiometabolic risk, which can further impair insulin resistance in the metabolism of individuals with MS. 34 The results of this study showed that the hypertensive elderly individuals with MS and those who are obese had higher FRSs. MS significantly increased the chance of the elderly having a high CVR.…”
Section: Discussionmentioning
confidence: 63%
“…Nevertheless, accumulating data suggest that there is a significant heterogeneity between men and women developing the metabolic syndrome, in large part due to hormonal regulation of fat distribution and attendant metabolic abnormalities [24]. In particular, it seems that this difference may be attributed to the lack of estrogen and its effects on glucose and lipid metabolism, as well as in fat distribution [25,26]. Thus, it seems reasonable that further studies consider sex differences in relation to the parameters of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…The loss of estrogens with menopause is associated with an increase in intra-abdominal fat accrual and somewhat smaller loss in lean body mass [16]. Men, due to anabolic and adipose-regulating effects of testosterone are characterized by higher lean mass and abdominal adiposity [13,17].…”
Section: Discussionmentioning
confidence: 99%